Tool (crates) to reduce post-harvest losses for tomatoes - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Interventions were implemented, tested, and monitored in pilot projects, followed by an evaluation workshop. 89% of participants bought crates. Approach resulted in context-specific, locally owned interventions to reduce postharvest losses in tomato value chains in Nigeria.